'Transgender Persons (Protection of Rights) Act' of India: An Analysis of Substantive Access to Rights of a Transgender Community. (11th April 2022) - Bhattacharya, Shamayeta; Ghosh, Debarchana; Purkayastha, Bandana
Abstract: The amendments to the Transgender Persons (Protection of Rights) Act of India in 2019 address non-binary persons' constitutional rights, recognition of their gender identity, and non-discrimination laws across institutional spaces (for example, family, workplace, education, and healthcare). The Act discusses legal rights in isolation of praxis, structural support and, more importantly, lacks guidelines needed to substantively access rights. Such a disconnection relegates human rights to merely legal changes with limited practice. In this article, we discuss the achievements and failures of the act from the perspective of a transgender community in India, and the impact it has had on their lives from its formulation in 2014. Although non-binary communities are recognized, they face severe abuse and discrimination. We analyse accounts of 15 transgender persons' lived experiences and challenges they faced in claiming their rights in Kolkata, a metropolis in eastern India. We used the framework of substantive access to rights, that is, the actual ability to practice and access documented rights, to critically discuss our findings across family, work, education, and healthcare spaces, often showing the gaps between achieved legal status, and the practical realities on the ground. We provide several recommendations to bridge these gaps—improving educational equity for non-binary people, including transgender specific training for healthcare providers and, more importantly, increasing the adequate representation of non-binary people in the positions of negotiation. The road to claiming social and economic rights following legal rights for non-binary gender communities cannot be achieved without overcoming their erasure within families and hypervisibility in public spaces.